The Effect of Index Card Match Strategy on Students' Achievement in Reported Speech (A Study at the Eleventh Grade Students of SMA Negeri 5 Padangsidimpuan) - SRI WAHYUNI HASIBUAN (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The objective of this research is to know whether there is a significant effect of index card match strategy on students’ achievement in reported speech at the eleventh grade students of SMA Negeri 5 Padangsidimpuan. This research uses experimental method with pre-experimental research design; one group pre-test post-test design. The population is all of the eleventh grade students which consists of 178 student. Technique sampling that used on this research is systematic simple sampling and the number of the sample consists of 30 students. In collecting the data, the researcher uses observation sheet to get the data of the application of index card match strategy and test to get the data of the students’ achievement in reported speech. The researcher uses statistic process in analyzing by using t test formula. Based on the data that had been analyzed, the result of data analyzing showed that t count is higher than t table (t count 9.33 > t table 2.04). So, the hypothesis is accepted. It means that there is a significant effect of index card match strategy on students’ achievement in reported speech at the eleventh grade students of SMA Negeri 5 Padangsidimpuan. Keywords: index card match strategy, reported speech.